Preservation approaches for milk and milk products: A Review - Verma, Taurn; Aggarwal, Ankur (Indian Journal of Dairy Science, 2022)
This review article summarizes the effect of formalin and other recommended preservatives on the chemical composition of milk and milk based other traditional dairy products including khoya, paneer, ice cream and other dairy products as well as its impact on the shelf life extension. Formalin (0.4%) is the only legally permissible preservative according to the Food Safety and Standard Regulations, 2011. Formalin is an antibacterial compound commonly used in preservation of organ specimens. It degrades nucleic acids by alkylation of amino, carboxyl or hydroxyl groups. All microorganisms including spore forming ones are rendered inactive. Although formalin's preservative action is quite effective, there are conflicting and contradictory data in the literature regarding the influence of formalin in terms of estimating major milk ingredients i.e. milk fat, protein, lactose etc. which is primarily used in the commercial production of dairy products. There is a need to produce a viable formalin substitute. For the preservation of dairy products mercuric chloride, potassium dichromate, alcohol, chloroform, ether, hydrofluoric acid, bronopol and other preservatives can be efficiently used. In view of the below discussion, it is clear that the use of preservatives other than formalin for milk and milk product samples intended for analytical purposes needs to be reconsidered.